Eksplorasi Jenis Bambu di Kecamatan Rawas Ulu Kabupaten Muratara - Reny Dwi Riastuti; Yuli Febrianti; Trisnawati Panjaitan (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2019)
This study aims: (1). To eksploration the type of Bamboo (Bambusa sp) in Rawas Ulu District, Muratara Regency. Data collection techniques in this study are as follows: (a). eksploration (b) Interview (c). Documentation; The research procedure is observation, location research, sample analysis, sample identification, sample description, ecological factors, bamboo benefits; (1). The results of identification there are 4 genera consisting of (Gigantochloa, Bambusa, Densrocalamus, and Schizoctachyum). There are 6 species consisting of (Gigantochloa apus, Gigantochloa pseudoarundin, Bambusa vulgaris, Bambusa glaucescens, Schizoctachyum blumei, Densrocalamus asper); (2). The ecological factors of bamboo are soil pH of 4.9-7.0 and air temperature of 25-30oC with soil moisture of 51-71%; (3). Bamboo can be used as light construction materials such as livestock pens, fences, ornamental plants, household handi crafts and woven industries. The conclusion of this study is that there are 4 genera and 6 types of bamboo that live differently. Keywords: eksploration, bambu